Coincidence Point Theorems for (α,β,γ)-Contraction Mappings in Generalized Metric Spaces - Chaiporn Thangthong; Anchalee Khemphet (International Journal of Mathematics and Mathematical Sciences)
The result of our study is that a coincidence point of two mappings P and Q can be achieved when the ordered pair (P,Q) is an (α,β,γ)-contraction with respect to a generalized metric space. Moreover, with some additional condition, a common fixed point can be obtained as a consequence of our main theorems. Further, we apply our findings to some examples and integral equation problems.